Pengaruh Kepribadian dan Dukungan Organisasi Terhadap Kepuasan Kerja Dimediasi oleh Motivasi: Studi Terhadap Pegawai di CV. Cahaya Karunia Di Brebes - Joshua Vincent Oktaviadi; Tristiana Rijanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the influence of personality and organizational support on job satisfaction with motivation as a mediating variable in CV. Cahaya Karunia. This research uses primary data obtained from respondents through questionnaires. The research population consisted of all employees at CV. Cahaya Karunia, Brebes City, numbering 100 people. The sampling technique was carried out using Purposive Sampling, namely sampling based on the criteria: permanent employees with work experience of more than 2 years and a high school education of 87 respondents. Data analysis uses multiple linear regression. Data processing uses SPSS 24.0. The results of hypothesis testing show that personality has a positive and significant effect on motivation. Organizational support has a positive and significant effect on motivation. Personality has no effect on Job Satisfaction. Organizational support has a positive and significant effect on job satisfaction. and Motivation has a positive and significant effect on job satisfaction.